2017
DOI: 10.1093/ofid/ofw240
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV) Quality Indicators Are Similar Across HIV Care Delivery Models

Abstract: Background.There are limited data on human immunodeficiency virus (HIV) quality indicators according to model of HIV care delivery. Comparing HIV quality indicators by HIV care model could help inform best practices because patients achieving higher levels of quality indicators may have a mortality benefit.Methods.Using the Partners HIV Cohort, we categorized 1565 patients into 3 HIV care models: infectious disease provider only (ID), generalist only (generalist), or infectious disease provider and generalist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This result is not surprising since ART in Israel is given in specialized centers with qualified teams, which as reported previously improves treatment outcomes. 25…”
Section: Discussionmentioning
confidence: 99%
“…This result is not surprising since ART in Israel is given in specialized centers with qualified teams, which as reported previously improves treatment outcomes. 25…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to differences in confidence related to the general care of PLWH versus care for specific non-HIV conditions as our study did not specifically ask about confidence in non-HIV care abilities. Earlier studies have shown that HIV specialists provide the majority of primary care for PLWH and patients cared for by HIV specialists have experienced better HIV associated outcomes than cared for by primary care providers [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A study of patients in care for HIV infection in Ontario, Canada found colorectal cancer screening was more common among patients receiving care from both generalists and specialists, compared with only HIV specialists [ 26 ]. A recent study comparing HIV care models found only minor differences in HIV quality metrics and processes of care when care was provided by generalists only, ID providers only, or both (ie, shared care) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%